2011
DOI: 10.1177/1461444811428899
|View full text |Cite
|
Sign up to set email alerts
|

Filtering 2008 US presidential election news on YouTube by elites and nonelites: An examination of the democratizing potential of the internet

Abstract: The goals of this study are to explore several claims about the democratizing potential of the internet and to extend gatekeeping theory into user-generated content (UGC) domain. A quantitative content analysis of the most popular YouTube political news videos during the 2008 US presidential election was conducted to investigate the degree to which nonelites were able to partake in mainstream public discourse. We found that elites dominated first and second filters (news sourcing and news production) in the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 30 publications
0
31
1
2
Order By: Relevance
“…Interactivity tools like retweets and hashtags were seldom used and, in contrast to Habermasian ideals of inclusion of peripheral actors, the nodes in discussion networks seemed to be the "old" elites. This is also the case with other social media like YouTube: Dylko et al (2011) show that, while non-elites have entered the discourse, the old elites keep a dominant position. Murphy (2011) points out that access to Twitter is "a socially stratified practice", as most low-income households worldwide have limited Internet access and-more importantly-low levels of digital literacy.…”
Section: Twitter and Election Campaignsmentioning
confidence: 71%
“…Interactivity tools like retweets and hashtags were seldom used and, in contrast to Habermasian ideals of inclusion of peripheral actors, the nodes in discussion networks seemed to be the "old" elites. This is also the case with other social media like YouTube: Dylko et al (2011) show that, while non-elites have entered the discourse, the old elites keep a dominant position. Murphy (2011) points out that access to Twitter is "a socially stratified practice", as most low-income households worldwide have limited Internet access and-more importantly-low levels of digital literacy.…”
Section: Twitter and Election Campaignsmentioning
confidence: 71%
“…Perhaps the gatekeeper perceived more credibility, professionalism, and analytical skills in the tweets from media-related professionals. Nevertheless, the tendency to use elite sources in on-screen visuals was supported, just as previous research in social media has found a continued reliance on elites (e.g., Dylko et al, 2012). Our findings lend support to the Internet and social media skeptics who do not anticipate that new technologies will change the elite bias in news coverage and that elites will somehow fail to find a way to dominate the newest technology (R. Davis & Owen, 1998;Winner, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Research on Internet blogs found a gatekeeping process in place where large blogs function as opinion leaders for smaller blogs, and moderation of large blogs enabled a structure for editorial gatekeeping to occur (Haas, 2005). New social media formats have also been found to highlight public figures and elites when compared with average citizens on popular Internet venues, such as YouTube (Dylko, Beam, Landreville, & Geidner, 2012). Previous research has also found that the integration of audience participation into traditional formats of journalism, such as the integration of received text messages from audience members into news production, utilized a gatekeeping process that left the moderator to select and edit messages (Enli, 2007).…”
Section: Gatekeeping and Social Mediamentioning
confidence: 93%
“…Así, distintos autores se han centrado en el efecto de redes digitales concretas como Twitter o Facebook sobre las campañas electorales en distintos países del mundo (Williams y Gulati, 2013), las revueltas políticas o los procesos de acción colectiva (Bennett y Segerbert, 2013;Dylko et al, 2012). Estos estudios, en mayor o menor medida, están dirigidos a medir el efecto de distintas prácticas realizadas a través de las redes sociales digitales sobre la relación entre ciudadanos o, entre estos, y sus representantes (Dalton, 2010).…”
Section: Participación Política E Internetunclassified